Effectiveness of Ustekinumab on Crohn's Disease Associated Spondyloarthropathy: Real-World Data from the Sicilian Network for Inflammatory Bowel Diseases (SN-IBD). (1st November 2020) - Macaluso, Fabio Salvatore; Fries, Walter; Viola, Anna; Costantino, Giuseppe; Muscianisi, Marco; Cappello, Maria; Guida, Laura; Giuffrida, Enrica; Magnano, Antonio; Pluchino, Dario; Ferracane, Concetta; Magrì, Giovanni; et al.
ABSTRACT: Background: The effectiveness of Ustekinumab (UST) on Crohn's disease (CD)-associated spondyloarthropathy (SpA) is currently unknown. Research design and methods: All consecutive CD patients with active SpA at the initiation of the treatment with UST were extracted from the cohort of the Sicilian Network for Inflammatory Bowel Diseases (SN-IBD). The primary outcome was the articular response at 8 and 24 weeks, defined as the disappearance of objective signs of arthritis (swelling and/or articular stiffness) and resolution of pain. Results: Thirty CD patients with active SpA at the initiation of the treatment with UST were assessed. At 24 weeks, 13 patients (43.3%) had an articular response, including 10/18 patients (55.5%) with peripheral SpA and 3/9 patients (33.3%) with axial and peripheral SpA. No patient with axial SpA experienced an articular response. The drop of mean as Harvey-Bradshaw Index values from baseline to week 24 was higher in patients with articular response compared with non-responders (3.8 ± 2.4 vs. 1.3 ± 2.8, p = 0.02). Conclusions: Our real-world, multicentre experience showed that UST was able to obtain a response on articular symptoms in nearly half of the patients with CD and active SpA after 24 weeks of treatment.